2008
DOI: 10.1186/1471-2334-8-104
|View full text |Cite
|
Sign up to set email alerts
|

Early indicators of exposure to biological threat agents using host gene profiles in peripheral blood mononuclear cells

Abstract: Background: Effective prophylaxis and treatment for infections caused by biological threat agents (BTA) rely upon early diagnosis and rapid initiation of therapy. Most methods for identifying pathogens in body fluids and tissues require that the pathogen proliferate to detectable and dangerous levels, thereby delaying diagnosis and treatment, especially during the prelatent stages when symptoms for most BTA are indistinguishable flu-like signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Human PBMC exposed to virus is a model for the viremic stage of infection in vivo when much of the transcriptome response is due to non-infectious signal transduction by viral particles [31] [24]. PBMC were used here and in other studies [32] [33] [34] rather than cell lines [35] [36] to more closely simulate the situation in vivo in which circulating blood cells are exposed to virus-infected sites. Here we have shown that in vitro PBMC exposure to arenaviruses with different pathogenic potential, LASV and ML29, resulted in differential expression of ISG, apoptotic, NF-kB, and coagulation pathway genes.…”
Section: Introductionmentioning
confidence: 99%
“…Human PBMC exposed to virus is a model for the viremic stage of infection in vivo when much of the transcriptome response is due to non-infectious signal transduction by viral particles [31] [24]. PBMC were used here and in other studies [32] [33] [34] rather than cell lines [35] [36] to more closely simulate the situation in vivo in which circulating blood cells are exposed to virus-infected sites. Here we have shown that in vitro PBMC exposure to arenaviruses with different pathogenic potential, LASV and ML29, resulted in differential expression of ISG, apoptotic, NF-kB, and coagulation pathway genes.…”
Section: Introductionmentioning
confidence: 99%
“…The Trizol isolated RNA was used in cDNA microarrays analysis. 21 For oligonucleotide microarrays, total RNA was isolated using PAXgene tubes following the manufacturer's protocol. Isolated RNA samples were stored at –80 °C until they were used for microarray and real-time PCR analyses.…”
Section: Methodsmentioning
confidence: 99%
“…A laser detection system was used (GenePix 4000b, Axon Instruments, CA) to scan the finished slides. The intensity of the scanned images was digitalized through Genepix 4.0 software (Axon Inc., CA) [26].…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Experiment was performed using 18S rRNA as the reference for quantitation as described in the Materials and Methods. The primer set was designed specifically for individual pathogen or toxin as described elsewhere(26).…”
mentioning
confidence: 99%